Rights of grievance and denunciation in the 2013 Constitution and some mechanisms to ensure the exercise of the rights of grievance and denunciation - Vu, Thi Nga (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
Human rights, rights, and obligations of citizens are important contents affirmed and recorded in the 2013 Constitution - the supreme legal document of the Socialist Republic of Vietnam. Among the groups of human rights recognized in Chapter II of the 2013 Constitution, the right of grievance and denunciation, in particular, are fundamental rights closely associated with state management activities, serving as a means to express the democratic rights of the people and exercise their oversight over the state apparatus. This article provides an overview of human rights; the right of grievance and denunciation; legal provisions on grievances, denunciations, and some mechanisms to ensure the exercise of the right of grievance and denunciation at present. This presents evaluative viewpoints and directions for further improvement to enhance the effectiveness of exercising these rights in practice